Escape room jako metoda aktywizująca w nauczaniu języka niemieckiego na uczelni wyższej - Łagowska, Kinga (Neofilolog, 2024)
The idea of using an escape room in foreign language teaching fits perfectly with the needs of today’s learners, where we create a natural learning environment using digital tools. In the winter semester 2022/2023, a project entitled ‘My linguistic Escape Room (ER)’ was carried out among 60 third-year undergraduate students of German Studies at the University of Warsaw Institute of German Studies as part of the subject ‘Contemporary trends in language learning’. This project comprised three phases and was preceded by theoretical and practical lectures on the specifics of ER, as well as a review of analogue and digital games. The initial part of the project consisted of the lecturer initiating the project, discussing topic proposals in a forum, dividing into teams and developing a preliminary project plan. The core part involved independent work in teams and the final part involved the presentation of ER scenarios to the forum and their evaluation. Each of these parts was carried out exclusively in German. The following article presents the results of the project. The tool used to collect the research material was a questionnaire. The aim of the study was to identify the opinions of 3rd year undergraduate German studies students on the use of escape rooms in higher education. The main part of the survey concerns the advantages and difficulties experienced during each of the three phases. In the final section of the survey, students declare a desire for further escape room games at university and also during their further academic career. This fact reinforces the belief that escape rooms are an interesting and engaging activation technique at university, which should become a permanent part of the teaching repertoire.